CONTRIBUTION OF SERVICE QUALITY ON CUSTOMER SATISFACTION - Abule Denboba, Wendmu (Journal of process management and new technologies, 2020)
Customer satisfaction has significant importance in corporate sector because without satisfied and loyal customers, you don't have a business. The benefit of customer satisfaction cannot be ignored because satisfied customers are like free promotion. Thus it is mandatory to providing a qualified service for them to achieve the above objective. Thus; this article analyzed the contributions of service quality for customer satisfaction in selected branches of commercial bank of Ethiopian in Jimma district. For the study both primary and secondary sources of data were employed; primary data were collected from customers and customer service managers of selected branches by using questionnaire and interview.  Convenience and judgmental sampling technique was used to get appropriate respondents. A total sample size of 385 customers, and 5 mangers were selected using Kothari’s sample size determination algorithm. Descriptive research design approach was applied conduct the study. The result reveals: all service quality dimensions (tangibles, responsiveness, empathy, assurance & reliability) has a positive contribution for customer satisfaction. The researcher recommended to the district that; though the mean result indicates existence of positive contributions of service quality to customer satisfaction: the value is not as such delight-full and cannot be a guaranty for customers to re-purchase. Thus; CEO need to conduct market research about problems limited them not to make customers delight-full.